Soil properties and carbon stock along the toposequence of Lalmai hill ecosystem of Bangladesh (Dhaka University Journal of Biological Sciences, 2021)
A study was carried out in the Lalmai hill ecosystem of Bangladesh regarding their soil properties and soil organic carbon (SOC) stocks. The Lalmai hill ecosystem consists of three toposequence arrangements as hills, piedmonts, and floodplains. Forty-five soil samples covering nine soil profiles were selected to conduct the present study. Soil samples were collected at five different depths of 0-20 cm, 20-40 cm, 40-60 cm, 60-80 cm and 80-100 cm intervals from each pit of the study sites. Soil pH, percent SOC, percent total nitrogen (TN), bulk density, cation exchange capacity (CEC), particle size distribution, and SOC storage (kg/m2) dataset indicates that piedmont deposits and floodplain soils are more enriched than the upper hill soils. Regarding SOC storage, the post hoc test indicates that hill soils are significantly different from the other two physiographic units, but there is no significant difference between piedmont deposits and floodplain soils. The soil property varies differently depending on their depth level at different physiographic units. Estimation on SOC stock revealed that 2.01Tg, 21.75Tg, 12.68Tg carbon remains in the hill soils, piedmont soils, and estuarine floodplain soils, respectively. The total SOC stock was estimated at 36.44 Tg in the Lalmai hill ecosystem of Bangladesh, where piedmont deposits contained the highest level of SOC stock. It is assumed that more clay-organic substances are washed in at the foot of piedmont units due to the well-drained nature of upper Pleistocene hill soils. Thus, fine soil textural nature, diverse land and land cover accelerates to sequester more carbon in piedmont zone rather than hill or floodplain zones.Dhaka Univ. J. Biol. Sci. 30(2): 331-343, 2021 (July)